2011
DOI: 10.1007/s10661-011-2431-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of urban sprawl and urban landscape pattern in a rapidly developing region

Abstract: Urban sprawl is a worldwide phenomenon happening particularly in rapidly developing regions. A study on the spatiotemporal characteristics of urban sprawl and urban pattern is useful for the sustainable management of land management and urban land planning. The present research explores the spatiotemporal dynamics of urban sprawl in the context of a rapid urbanization process in a booming economic region of southern China from 1979 to 2005. Three urban sprawl types are distinguished by analyzing overlaid urban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(23 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…Except for a few cities in the PRD urban megaregion, cities in the three urban megaregions were mostly dominated by growth of edge-expansion and leapfrogging, which may be linked with urban sprawl, or low land efficiency [15,50]. It is widely recognized that urban sprawl may lead to not only environmental and ecological issues (e.g., loss of open space and wildlife habitat, increased surface runoff and flooding, and air pollution) but also social problems and health issues (e.g., increased expenditure in public services and thus taxes, increasing traffic congestion and obesity [51][52][53][54].…”
Section: Discussionmentioning
confidence: 99%
“…Except for a few cities in the PRD urban megaregion, cities in the three urban megaregions were mostly dominated by growth of edge-expansion and leapfrogging, which may be linked with urban sprawl, or low land efficiency [15,50]. It is widely recognized that urban sprawl may lead to not only environmental and ecological issues (e.g., loss of open space and wildlife habitat, increased surface runoff and flooding, and air pollution) but also social problems and health issues (e.g., increased expenditure in public services and thus taxes, increasing traffic congestion and obesity [51][52][53][54].…”
Section: Discussionmentioning
confidence: 99%
“…The Yangtze River Delta Urban Agglomeration presents multiple interconnected centers (Suzhou, Hangzhou, Nanjing, Ningbo and Wuxi) besides the centrally placed Shanghai, which in turn encourages growth in neighboring cities/towns (Zhu & Zheng, 2012). For the Pearl River Delta Urban Agglomeration, although Guangzhou and Shenzhen are also the "double-nuclei", other cities all have a clear specialization of leading industry and traffic network among cities is well developed (Lv et al, 2012). In contrast, although Beijing, Tianjin and Shijiazhuang were all stimulated by the Regional Development of the Jing-Jin-Ji Urban Agglomeration and had a breakthrough during 2005-2010 in urban expansion (evidenced by striking rise of urban land in both area and rate), substantive regional integration is far from realization for this region.…”
Section: Comparisons In the Magnitude Of Urban Expansion Among Three mentioning
confidence: 99%
“…The three largest urban agglomerations (i.e., the Yangtze River Delta, the Pearl River Delta and the Jing-Jin-Ji) have pioneered the nation in urbanization processes. Although many studies can be found focusing on urban expansion in the Yangtze River Delta (Tian, Jiang, Yang, & Zhang, 2011;Xu, Liu, & Zhang, 2007;Yue, Liu, & Fan, 2013) and the Pearl River Delta (Lv, Dai, & Sun, 2012;Seto & Kaufmann, 2003;Sun, Wu, Lv, Yao, & Wei, 2013), few were on the Jing-Jin-Ji Urban Agglomeration (He, Tian, Shi, & Hu, 2011;Tan, Li, Xie, & Lu, 2005;Xiao et al, 2006). Particularly, cross-city comparative studies employing spatially explicit and consistent data sets, especially with high temporal frequency of snapshots of urban conditions over long time periods, and landscape ecology approaches are sorely lacking in the region.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the diversity and heterogeneity of landscape [35,36], five representative landscape-level metrics characterizing the urban sprawl were calculated by Fragstats 4.0 based on the resampled land use maps with a resolution of 1 kmˆ1 km [37]. The metrics include Aggregation index (AI), Contagion index (CONTAG), Landscape shape index (LSI), Perimeter-area fractal dimension (PAFRAC), and Shannon's diversity index (SHDI).…”
Section: Landscape Patternmentioning
confidence: 99%